Students’ Perception of Religious Character Education Value in Novel “di Bawah Langit Yang Sama” - Hetilaniar Hetilaniar (AL-ISHLAH: Jurnal Pendidikan, 2022)
Therefore, this study aims to determine student perceptions of the value of religious character education contained in the novel entitled “Di Bawah Langit Yang Sama”. Qualitative research methods have become research procedures. Data were taken from student learning activities through novels and interviews. The data sources were students and they were 100 students (M = 57, F = 43). Data analysis techniques include (1) problem formulation, (2) selection or categorization of data sources, (3) elaboration of data categories based on operational definitions, (4) checking reliability, (5) data analysis, research, reports and evaluation of research results. Checking the validity of research data using credibility, transferability, triangulation, dependability, and confirmability. The results of the study conclude that religious values describe the way a person communicates and worships God, how to pray, carry out God's commands, preserve customs related to worship ceremonies, and respect each other to live in harmony. The implications of the results of this study have taught students to understand the value of local wisdom and preserve various traditional values that have become the customs of people's lives.